Pengaruh Store Atmosphere, Lokasi, Dan Keragaman Produk Terhadap Keputusan Pembelian Pakaian: Pada Pasar Umum Pasirian Lumajang - Sufyan Lutfi; Jesi Irwanto (Jurnal Ilmu Manajemen Advantage, 2017)
This study aims to determine the of store atmosphere, location, and product diversity on the purchasing influence decision to buy clothes on the general market of Pasirian Lumajang. This research is a quantitative research by finding associative ssociation which is causal. The results of this study showes that partially store tmosphere has no significant effect on purchasing decisions, location has a significant influence on purchsing decisions, and product diversity has a significant effect on purchasing decisions. Simultaneously store atmosphere, location, and product diversity have a significant effect on purchasing decision of garment at general market of Pasirian Lumajang. The limitations of this study is to research of store atmosphere, ocation, and product diversity as a factor influencing purchasing decisions, while ther variables that can influence purcasing decisions are expected to be examined by subsequent researchers in different periods and internet services.